STABILITY ANALYSIS OF THE POWER SYSTEM AT THE BANTEN 3 LONTAR COAL-FIRED POWER PLANT WITH THE INSTALLATION OF A POWER SYSTEM STABILIZER ON THE 150KV TRANSMISSION SYSTEM OF TELUK NAGA TANGERANG BARU SINDANG JAYA - Arief , Muhammad; Suwandi, Suwandi; Kustiawan , Eko; Jefri Anarkhi, Jefri Anarkhi (Journal of Industrial Engineering & Management Research, 2024)
In the operation of the electric power system, there are often short circuit disturbances, both permanent and temporary, the use of the connection can cause deviations in the variable variables of the electric power system, such as voltage, frequency.The load growth on the 150 kV Teluk Naga Tangerang Baru Sindang Jaya (Tangerang) Banten network system is increasing day by day. The cause is the current development of development. The growth of the load increases the possibility that the number of loads will exceed the existing generation capacity in the future. With the growth of the load that continues to increase, the possibility of blackouts increases if at any time there is a problem with one of the plants. Therefore, this is a concern by PLN on plants that are not equipped with equipment to increase transient stability. For this reason, the Banten 3 Lontar PLTU needs a Power System Stabilizer on the generator. Before activating this feature, it is necessary to conduct a transient stability analysis to determine the system's response to the network it is supplied with. Observation of the changes that occur will show how much the Power System Stabilizer has an effect on increasing transient stability. In the final result, it can be seen that the transient stability increases after the use of the Power System Stabilizer